2020
DOI: 10.1074/jbc.ra120.012793
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ biosynthesis in bacteria is controlled by global carbon/nitrogen levels via PII signaling

Abstract: Nicotinamideadenine dinucleotide (NAD + ) is a central metabolite participating in core metabolic redox reactions. The prokaryotic NAD synthetase enzyme NadE catalyzes the last step of NAD + biosynthesis, converting nicotinic acid adenine dinucleotide (NaAD) to NAD + . Some members of the NadE family use L-glutamine as a nitrogen donor and are named NadE Gln . Previous gene neighborhood analysis has indicated that the bacterial nadE gene is frequently clustered with the gene encoding the regulatory signal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…A variety of key metabolic enzymes, transcription factors, and transport proteins use this signaling path to tune their activity in response to the metabolic state. P II in its different conformations can directly interact with various target proteins such as the N-acetyl- l -glutamate kinase, catalyzing the committed step in arginine biosynthesis ( 7 , 8 ); the acetyl-CoA carboxylase, catalyzing the rate-limiting step in fatty acid biosynthesis ( 9 ); the phosphoenolpyruvate carboxylase, which catalyzes an anaplerotic carbon fixation ( 10 ); or the glutamine-dependent nicotinamide adenine dinucleotide (NAD + ) synthetase ( 11 ). Besides tuning the activity of enzymes, recent analyses revealed that, through direct protein–protein interaction, the abundant P II proteins can also regulate transport activities, including an ensemble of nitrogen transporters such as the nitrate/nitrite transport system, the urea transport system, and the ammonium transporter ( 12 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of key metabolic enzymes, transcription factors, and transport proteins use this signaling path to tune their activity in response to the metabolic state. P II in its different conformations can directly interact with various target proteins such as the N-acetyl- l -glutamate kinase, catalyzing the committed step in arginine biosynthesis ( 7 , 8 ); the acetyl-CoA carboxylase, catalyzing the rate-limiting step in fatty acid biosynthesis ( 9 ); the phosphoenolpyruvate carboxylase, which catalyzes an anaplerotic carbon fixation ( 10 ); or the glutamine-dependent nicotinamide adenine dinucleotide (NAD + ) synthetase ( 11 ). Besides tuning the activity of enzymes, recent analyses revealed that, through direct protein–protein interaction, the abundant P II proteins can also regulate transport activities, including an ensemble of nitrogen transporters such as the nitrate/nitrite transport system, the urea transport system, and the ammonium transporter ( 12 ).…”
mentioning
confidence: 99%
“…In a previous P II protein interaction study, several putative P II interactors of unknown function were identified ( 12 ). The most prominent hit was the product of the sll0944 gene, a member of the NtcA regulon ( 11 , 13 ). The sll0944 gene product is annotated in Uniprot ( https://www.uniprot.org/uniprot/P77971 ) as a protein of unknown function.…”
mentioning
confidence: 99%
“…Two isoforms of the glutamine-dependent NAD synthetase (NadE1 and NadE2) and the enzyme involved in coenzyme A biosynthesis (CoaBC) were identified as potential GlnZ targets ( Table 1 ). The NadE2 enzyme has been studied as a GlnZ target in A. brasilense previously ( 26 ). Upon an ammonium shock, GlnZ interacts with NadE2 to relieve the NAD + negative-feedback inhibition over the NadE2 enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work in bacteria and plants revealed several novel PII targets that are not only involved in nitrogen metabolism, but in general core metabolism, such as acetyl-coenzyme A (CoA) carboxylase, phosphoenolpyruvate carboxylase (PEPC), NAD synthetase, and glucosamine 6-phosphate deaminase ( 25 27 ). Therefore, PII has a much broader regulatory role than originally thought.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation